Swelling Potential and Mineralogy of Al-Hartha City Soil in Basrah-Southern Iraq - Younis, Saja N.; Mahmood, Ra’id A.; Alsaad, Harith A. (Iraqi Journal of Science, 2024)
Mineralogical and geotechnical properties used to analyse the swelling potentials of Al-Hartha City. According to mineralogy, montmorillonite is a dominated clay mineral (33.61%) followed by montmorillonite-chlorite (33.34%), kaolinite (9.18%) and illite (5.38%). While calcite, Quartz, Feldspar, and dolomite are non-clay minerals that are also present. According to geotechnical analysis, the percent of clay range between 9-42% with an average of 25.5%, silt 55-80% with an average of 67.5% and sand 0-17% with an average of 8.5%. While liquid limits and plasticity index are, respectively, 10–25% with an average of 17.5% and 35%–51% with an average of 43%. According to the unified soil classification system (USCS), these soils are mainly low plasticity lean clay soils (CL) and 10% classified as medium stiff elastic silt (MH). According to activity values, soils are primarily inactive-(70%), normally active-(20%), active-(10%), and their consistency is plastic. according to an assessment of soil expansivity based on index properties and activity, a significant amount of the soil is expansive. Additionally, there is an agreement between the results of the mineralogical tests performed on these soils and the results of the measures of soil expansivity obtained from the evaluation of the swelling of the soil based on assessments of its index properties.